2023
DOI: 10.1111/1750-3841.16472
|View full text |Cite
|
Sign up to set email alerts
|

Study on structural characteristics and physicochemical properties of starches extracted from three varieties of kudzu root (Pueraria lobata starch)

Abstract: Kudzu root (Pueraria lobata) is well known for its traditional use as a medicinal food homologous plant in China. Three varieties of kudzu roots, such as Gange-1, Gange-2, and Gange-6, are commonly used. Nowadays, kudzu starch (KS) is commercially available as satiating foods or product ingredients. Differentiation and selection of the variety are important components of quality control for KS-based products. Thus, the present work was aimed at comparing the physicochemical properties, such as thermodynamic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Of the functional components, kudzu starch is frequently utilized as a functional food for the management of type 2 diabetes mellitus (T2DM) [ 125 ]. Studies have demonstrated that there are variations in the thermodynamic properties, pasting properties, solubility, swelling, and structural characteristics of the starches extracted from different KR varieties [ 126 ]. KR is recognized for its high fiber content, which includes both soluble dietary fiber (SDF) and insoluble dietary fiber (IDF), with respective contents of 30% and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Of the functional components, kudzu starch is frequently utilized as a functional food for the management of type 2 diabetes mellitus (T2DM) [ 125 ]. Studies have demonstrated that there are variations in the thermodynamic properties, pasting properties, solubility, swelling, and structural characteristics of the starches extracted from different KR varieties [ 126 ]. KR is recognized for its high fiber content, which includes both soluble dietary fiber (SDF) and insoluble dietary fiber (IDF), with respective contents of 30% and 10%.…”
Section: Discussionmentioning
confidence: 99%